The Efficiency of the Nigerian Stock Exchange: A Theoretical and Empirical Analysis - Ogege, Samson; Udoka, Chris O. (Indian Journal of Finance, 2012)
Growth is a key objective of developing nations, including Nigeria. However, inefficiency of stock markets can pose real dangers to the economic growth of any nation through misallocation of scarce investible resources. This study investigates weak-form of the Nigerian stock market in the context of the Efficient Market Hypothesis. The stock market prices were modeled to test for weak-form efficiency-the search for serial correlation, which will indicate whether or not current stock market prices depend on previous prices. Using monthly time-series data from 1985-2010, a unit root test and regression analysis involving both the least squares and two stage least squares estimation techniques was used to test efficiency of the Nigerian Stock Exchange. The results revealed that the market was not efficient and also indicates the presence of market seasonality. It is , therefore, recommended that there is a strong need to put in place policy measures that would guarantee competitive participation and avoid the "buy and hold" attitude of securities by investors which have delayed the rapid development of Nigeria's national economy.